Possibility and Development of Ski and Winter Adventure Tourism in Nepal Himalaya: Insights from Mera Peak - Paudel, Basanta; Sherpa, Tshiring Jangbu; Thapa, Bijaya; Thapa, Sewika (Journal of Tourism and Himalayan Adventures, 2022)
Adventure tourism is one of the main attractions in Nepal, however, ski and winter tourism are not famous yet. Therefore, this study carried out research on the possibility and development of ski adventure tourism in the favor of winter tourism. The Mera peak area has been selected as the study area, which is located in the Hinku Valley, Solukhumbu, at 6470-meter above sea level. This study used Remote Sensing approaches, a walk survey and photography, and conducted 27 Key Informant Interview (KII) to screen the possibility and development of the ski and winter tourism. Global Positioning System (GPS), Geographic Information System (GIS), and Satellite Images via Google Earth have been applied for route and ski sites mapping. Digital Elevation Model (DEM) data (12.5 m resolution) has been used for DEM, slope, hillshade, and contour analysis. Mann-Kendall trend test and Sen’s slope was applied to determine the climatic trend of the region. The study explored detailed route and ski sites of the Mera peak area and identified it as one of the potential areas for skiing in Nepal. There were not noticiable risk factors for skiing except climate change and minor crevasses. There are several destinations for ski activities in Nepal, which would promote winter tourism in the country. The study uncovered that there have been increasing rates of temperature and decreasing rates of precipitation in the mountain region of Nepal. These climatic factors added some level of risk for a ski industry in the region because increasing trends of temperature result in high rates of snow ablation. The findings of this research will greatly help to promote ski and winter tourism in Nepal, and it will be one of the base documents for developing ski- related policy by the government of Nepal and will be useful for further academic and scientific research in Nepal.